Ekspresi Sebab-Alasan (kara, node, dan te, de) dalam Kalimat Bahasa Jepang - Sri Iriantini (IZUMI, 2022)
Sentence patterns kara, node, and te, de, are used to convey the expression of reason-result. These four sentence patterns are used to express reason-result, each with slightly different meaning nuances. As because the expression of reason-result in Indonesian is not as complex and complicated as in Japanese, the existence of these different nuances of meaning frequently causes difficulties for foreign students studying Japanese, particularly students from Indonesia. The four sentence patterns of kara, node, and te, de which are descriptors of reasoning in Japanese, will be studied from the morphosyntactic and semantic sides to produce a clear description that can be used as a reference for Indonesian learners using cause expressions - the rationale. The research method employed was qualitative, with descriptive data presentation. The distributional method and a technique of sorting out certain elements were used for the research technique, while the distributional method and a technique of sorting out certain elements were used for the study technique. According to the findings of this study, the expressions of reason-result kara, node, and te/de each have a distinct use. The use of the type of verb or type of word in the first clause and the circumstances that occur in the second clause show a difference in usage and meaning. In some contexts, kara and node can be substituted for each other, whereas for te/de, which has a unity with the first and second clauses, substitution with kara or node is subject to certain conditions. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor